The Beta-Lactam Resistome Expressed by Aerobic and Anaerobic Bacteria Isolated from Human Feces of Healthy Donors - Rosalino Vázquez-López; Sandra Solano-Gálvez; Diego Abelardo Álvarez-Hernández; Jorge Alberto Ascencio-Aragón; Eduardo Gómez-Conde; Celia Piña-Leyva; Manuel Lara-Lozano; Tayde Guerrero-González; Juan Antonio González-Barrios (MDPI AG, 2021)
Antibiotic resistance is a major health problem worldwide, causing more deaths than diabetes and cancer. The dissemination of vertical and horizontal antibiotic resistance genes has been conducted for a selection of pan-resistant bacteria. Here, we test if the aerobic and anaerobic bacteria from human feces samples in health conditions are carriers of beta-lactamases genes. The samples were cultured in a brain-heart infusion medium and subcultured in blood agar in aerobic and anaerobic conditions for 24 h at 37 °C. The grown colonies were identified by their biochemical profiles. The DNA was extracted and purified by bacterial lysis using thermal shock and were used in the endpoint PCR and next generation sequencing to identify beta-lactamase genes expression (OXA, VIM, SHV, TEM, IMP, ROB, KPC, CMY, DHA, P, CFX, LAP, and BIL). The aerobic bacterias Aeromonas hydrophila, Citrobacter freundii, Proteus mirabilis, Providencia rettgeri, Serratia fonticola, Serratia liquefaciens, Enterobacter aerogenes, Escherichia coli, Klebsiella pneumoniae, Pantoea agglomerans, Enterococcus faecalis, and Enterobacter cloacae, the anaerobic bacteria: Capnocytophaga species, Bacteroides distasonis, Bifidobacterium adolescentis, Bacteroides ovatus, Bacteroides fragilis, Eubacterium species, Eubacterium aerofaciens, Peptostreptococcus anaerobius, Fusobacterium species, Bacteroides species, and Bacteroides vulgatus were isolated and identified. The results showed 49 strains resistant to beta-lactam with the expression of blaSHV (10.2%), blaTEM (100%), blaKPC (10.2%), blaCYM (14.3%), blaP (2%), blaCFX (8.2%), and blaBIL (6.1%). These data support the idea that the human enteric microbiota constitutes an important reservoir of genes for resistance to beta-lactamases and that such genes could be transferred to pathogenic bacteria.